The Study of Moroccan Judeo-Spanish (Hakitia) - Bentolila, Yaakov (MiKAN, 2007)
The Judeo-Spanish that was spoken in Morocco until two or three generations ago is known by the name “Haketia” This term (derived from Arabic) refers to the spoken language, the vernacular, which included an abundance of Arabic loan words. Formal literary registers of the language avoid Arabic words and therefore attain a high degree of uniformity with the general Ladino koine. Unlike its oriental Judeo-Spanish counterpart, Haketia, due to geographical proximity, preserved strong links with Spanish and was heavily influenced by it, to the extent that eventually, it was almost entirely replaced by the latter. Among members of former Haketia speaking communities, dispersed nowadays all overthe world, Haketia is no more than a source of household or cultural-religious expressions. Academic research into Haketia began with a literary focus, at the beginning of the XXth century. In a series of articles by Jose Benoliel, we find the first systematic linguistic description of this dialect. Since then, our knowledge has greatly increased, due to the work of dedicated researchers, especially Spanish scholars in the literary domain. Some of them treated linguistic issues, but the spoken aspects were rarely dealt with and, in general, the study of the Hebrew and Arabic components of this dialect was quite limited. In recent years, Haketia has begun to play an important role as a means of self-identification among Jews who emigrated from Spanish Morocco to other diasporas. Far from the former homeland, Haketia no longer represents a threat to successful cultural integration. Talented persons have now rejuvenated a kind of reconstructed Haketia, with a very salient humoristic character. Others are dedicating their efforts to the regathering of oral texts (such as proverbs), or to the sponsoring of academic work in this field.